High Acidity and Low Carbon-Coke Formation Affinity of Co-Ni/ZSM-5 Catalyst for Renewable Liquid Fuels Production through Simultaneous Cracking-Deoxygenation of Palm Oil - Didi Dwi Anggoro; Cokorda Satrya Pramana; Amalia Rizqi Ramadhani; Istadi Istadi; Teguh Riyanto (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
This study investigates the effect of chemically doped Co and Ni metals on ZSM-5 catalyst with respect to the catalysts’ characteristics and performance for palm oil cracking. Some characterization methods have been conducted to identify the physicochemical properties of the synthesized catalysts, including X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), N2-physisorption, NH3- and CO2-probed Temperature Programmed Desorption (NH3-TPD and CO2-TPD) methods. The deposited carbon-coke on the spent catalysts is analysed using simultaneous thermal gravimetric – differential scanning calorimetry (TG-DTG-DSC) analysis. The performance of catalysts was evaluated on palm oil cracking process in a continuous fixed-bed catalytic reactor at 450 °C. To determine the liquid product composition functional group and components, we used Attenuated Total Reflectance Fourier-transform Infrared Spectroscopy (ATR-FTIR) and batch distillation methods, respectively. We found that the Co metal chemically-doped on Ni/SM-5 catalyst, resulting the increase in the catalysts acidity and the decrease in catalysts basicity. The conversion of palm oil increases as the increase of the ratio of catalysts’ acidity to basicity. The highest triglyceride conversion (76.5%) was obtained on the 3Co-Ni/ZSM-5 with the yield of gasoline, kerosene, and diesel of 2.61%, 4.38%, and 61.75%, respectively. It was also found that the chemically doping Co metal on Ni/ZSM-5 catalyst decreased carbon-coke formation due to the low catalysts’ basicity. Overall, it is proven that the combination of Co and Ni, which chemically doped, on ZSM-5 catalyst has a good activity in palm oil conversion with low carbon-coke formation affinity and high acidity of catalyst.